Adapting Zero Trust: information security cultural factors considerations in the UAE context - Zyoud, Bader; Syheerah Lebai Lutfi, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study explores how cultural factors impact the adoption of Zero Trust Architecture (ZTA) within Middle Eastern culture, focusing on United Arab Emirates (UAE). The zero-trust security model, based on "never trust, always verify," challenges traditional models and is particularly relevant in cultural contexts divergent from Western practices. The study constructs a theoretical model based on common information security culture factors and zero trust adoption in the Arab cultural setting, utilizing data from a survey of 98 cybersecurity experts in the UAE. Using Partial Least Squares Structural Equation Modelling (PLS-SEM), this study tests hypotheses to determine the correlation between information security culture factors and the adoption of Zero Trust Architecture (ZTA). The findings reveal significant correlations between information security culture factors and ZTA adoption, including awareness and training (ATS), policy and procedure (PPS), security behaviour (SBS), communication (COMS), top management support (TMS), change management (CMS), information security management (ISMS), and compliance (CPS). Notably, ATS, PPS, SBS, and TMS show substantial positive correlations with ZTA adoption. However, change management (CMS) lacks a statistically significant correlation with ZTA adoption, indicating that introducing new technology itself is not a hindrance. This study establishes the positive and consistent influence of information security cultural factors on ZTA adoption, highlighting their critical role in achieving a more secure and zero trust network architecture. emphasizing the need for further research to refine conclusions by considering additional factors such as the original nationalities of participants, given the diverse population in the UAE.